2020
DOI: 10.1097/mat.0000000000000983
|View full text |Cite
|
Sign up to set email alerts
|

Bridge to Transplant with Ventricular Assist Device Support in Pediatric Patients with Single Ventricle Heart Disease

Abstract: Ventricular assist device (VAD) support for children with single ventricle (SV) heart disease remains challenging. We performed a single-center retrospective review of SV patients on VAD support and examined survival to transplant using the Kaplan–Meier method. Patients transplanted were compared with those who died on support. Between 2009 and 2017, there were 14 SV patients with 1,112 patient-days of VAD support. Stages of palliation included pre-Glenn (n = 5), Glenn (n = 5), and Fontan (n = 4). Eight patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
1
31
1
Order By: Relevance
“…Given donor shortage, there are many reports in recent years (2014-2019) of SVAD support for Fontan patients as BTT. 42,180,184,[193][194][195][196][197][198][199][200][201][202][203] There are also case reports of DT SVAD support for Fontan patients, 204 as well as VAD support of the pulmonary circulation. 205 Additionally, SVAD support in Fontan patients as bridge to combined multiorgan (heart-liver, heart-kidney) transplant have not yet been reported.…”
Section: Support Strategies For Single Ventricle Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given donor shortage, there are many reports in recent years (2014-2019) of SVAD support for Fontan patients as BTT. 42,180,184,[193][194][195][196][197][198][199][200][201][202][203] There are also case reports of DT SVAD support for Fontan patients, 204 as well as VAD support of the pulmonary circulation. 205 Additionally, SVAD support in Fontan patients as bridge to combined multiorgan (heart-liver, heart-kidney) transplant have not yet been reported.…”
Section: Support Strategies For Single Ventricle Patientsmentioning
confidence: 99%
“…Durable CF 184,[193][194][195][196][197][198]204 and PF devices, 180,[198][199][200][201] as well as temporary support devices, 202 have been used in Fontan patients as BTT. Recently, there has been increasing use of durable CF devices including the HeartMate 3 197 and HVAD.…”
Section: Support Strategies For Single Ventricle Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they noted that supporting SV patients with failing Fontan was generally successful in their experience, they reported significant mortality (80%) in those supported with the Glenn physiology. 9 They suggested either conversion to shunt physiology or moving on to Fontan operation plus simultaneous VAD as alternative ways to be able to support these patients given the numerous physiologic challenges in children with Glenn physiology that they described nicely in their discussion section. 9 It is likely that patient selection and institutional experience affect MCS outcomes in children with SVanatomy, and that might explain different results and conclusions from various institutions.…”
Section: Single Ventricle Anatomy and Vad Usementioning
confidence: 99%
“…9 They suggested either conversion to shunt physiology or moving on to Fontan operation plus simultaneous VAD as alternative ways to be able to support these patients given the numerous physiologic challenges in children with Glenn physiology that they described nicely in their discussion section. 9 It is likely that patient selection and institutional experience affect MCS outcomes in children with SVanatomy, and that might explain different results and conclusions from various institutions. Granegger and colleagues 10 reported outcomes of MCS in 33 children and found that MCS in children with SV anatomy was associated with inferior 1-year survival compared with patients with biventricular circulation (50% vs 80%).…”
Section: Single Ventricle Anatomy and Vad Usementioning
confidence: 99%